Normative Data of Dutch Idiomatic Expressions: Subjective Judgments You Can Bank on - Hubers, Ferdy; Cucchiarini, Catia; Strik, Helmer; Dijkstra, Ton (Frontiers in Psychology, 2019)
The processing of idiomatic expressions is a topical issue in empirical research. Various factors have been found to influence idiom processing, such as idiom familiarity and idiom transparency. Information on these variables is usually obtained through norming studies. Studies investigating the effect of various properties on idiom processing have led to ambiguous results. This may be due to the variability of operationalizations of the idiom properties across norming studies, which in turn may affect the reliability of the subjective judgements. However, not all studies that collected normative data on idiomatic expressions investigated their reliability, and studies that did address the reliability of subjective ratings used various measures and produced mixed results. In this study, we investigated the reliability of subjective judgements, and their impact on the participants’ idiom knowledge by collecting normative data of five idiom properties (Frequency of Exposure, Meaning Familiarity, Frequency of Usage, Transparency, and Imageability) for 374 Dutch idiomatic expressions from 390 native speakers. For reliability, we compared measures calculated in previous studies, with the D-coefficient, a metric taken from Generalizability Theory. High reliability was found for all dimensions. One reliability metric, Krippendorff’s alpha, generally produced lower values, while similar values were obtained for three other measures (Cronbach’s alpha, Intraclass Correlation Coefficient, and the D-coefficient). Advantages of the D-coefficient are that it can be applied to unbalanced research designs, and to estimate the minimum number of raters required to obtain reliable ratings. Slightly higher coefficients were observed for so-called experience-based dimensions (Frequency of Exposure, Meaning Familiarity, and Frequency of Usage) than for content-based dimensions (Transparency and Imageability). In addition, fewer raters were required to obtain reliable ratings for the experience-based dimensions. All idiom properties turned out to affect idiom knowledge. Meaning Familiarity, Frequency of Exposure, Frequency of Usage, and Transparency positively contributed to idiom knowledge, while a negative effect was found for Imageability. We discuss these relationships in more detail, and give methodological recommendations with respect to the procedures and the measure to calculate reliability.